2023
DOI: 10.1186/s12913-023-09342-6
|View full text |Cite
|
Sign up to set email alerts
|

The application of spatial measures to analyse health service accessibility in Australia: a systematic review and recommendations for future practice

Abstract: Background Australia's inequitable distribution of health services is well documented. Spatial access relates to the geographic limitations affecting the availability and accessibility of healthcare practitioners and services. Issues associated with spatial access are often influenced by Australia's vast landmass, challenging environments, uneven population concentration, and sparsely distributed populations in rural and remote areas. Measuring access contributes to a broader understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 114 publications
(263 reference statements)
0
6
0
Order By: Relevance
“…Distance to services is a significant barrier to accessing healthcare. Wood et al [ 91 ] in a systematic review, identified that there is a lack of research which measures spatial access specific to mental health services in Australia, and highlighted a need for consensus on what is reasonable access to healthcare services. Further, reports have noted that while distance alone is a significant barrier to accessing healthcare, accommodation may sometimes need to be sought depending on the time of the appointment, adding to the cost of attending the appointment [ 92 ] and further perpetuating the resource issues experienced by those living in rural areas of Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Distance to services is a significant barrier to accessing healthcare. Wood et al [ 91 ] in a systematic review, identified that there is a lack of research which measures spatial access specific to mental health services in Australia, and highlighted a need for consensus on what is reasonable access to healthcare services. Further, reports have noted that while distance alone is a significant barrier to accessing healthcare, accommodation may sometimes need to be sought depending on the time of the appointment, adding to the cost of attending the appointment [ 92 ] and further perpetuating the resource issues experienced by those living in rural areas of Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Health inequalities are an important challenge at the global level and require substantial investment in different regions. In order to identify geographic areas in terms of the health status of citizens, knowledge is needed in the decision-making and implementation of health policies in order to address the situation of inequalities, spatial measures, and coherent spatial classifications [1]. Accessibility to health centres and hospitals (HCHs), as defined by the World Health Organization (WHO), refers to the provision of health services that are easily and reasonably available to all segments of both urban and rural populations, with a particular focus on marginalised and underserved groups.…”
Section: Introductionmentioning
confidence: 99%
“…Equity of community access to centralised low-volume highly specialised healthcare services is desirable but complex to achieve and can be measured in a variety of ways. 1 Investigation of geographical and socioeconomic factors on access to healthcare services and resultant outcomes within Australia have demonstrated mixed results, often disproportionately affecting rural residents. [2] , [3] , [4] , [5] , [6] Extracorporeal membrane oxygenation (ECMO) is a form of advanced mechanical organ support for refractory cardio-respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…There are several well-described statistical methods to evaluate geographic access to, and utilisation of health services. 1 , 16 , 17 Choropleth maps are a common method of visually displaying data trends across a geographic region. 18 Spatial autoregression models permit analysis of geographical factors when healthcare access is subject to spatial lag, where an outcome variable in a location is influenced by both it and its neighbours’ independent and dependent variables.…”
Section: Introductionmentioning
confidence: 99%